Determinan Kinerja Keuangan Bank Umum Syariah di Indonesia - Al Parisi, Salman (IKONOMIKA, 2017)
This study aimed to know the effect of CAR, NPF, FDR, BOPO and NOM on ROA both of partially and simultaneously for year 2011-2016. This study uses Panel Data Regression. Furthermore, Object of research consists of Islamic Banking in Indonesia with annually data from 2011to 2016. The dependent variable (Y) used in this panel datais ROA and independent variables (X) consist of CAR, NPF, FDR, BOPO, and NOM. The results showed that CAR, NPF and NOM have significant positive effect on ROA, while FDR and BOPO have significant negative effect on ROA. In addition, CAR, NPF, FDR, BOPO, and NOM variables have significant effect on ROA of Islamic Banking simultaneously for 2011-2016.